2019
DOI: 10.1021/acs.jctc.9b01083
|View full text |Cite
|
Sign up to set email alerts
|

Is the Trotterized UCCSD Ansatz Chemically Well-Defined?

Abstract: The variational quantum eigensolver (VQE) has emerged as one of the most promising near-term quantum algorithms that can be used to simulate many-body systems such as molecular electronic structures. Serving as an attractive ansatz in the VQE algorithm, unitary coupled cluster (UCC) theory has seen a renewed interest in recent literature. However, unlike the original classical UCC theory, implementation on a quantum computer requires a finite-order Suzuki-Trotter decomposition to separate the exponentials of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 33 publications
8
153
0
Order By: Relevance
“…As mentioned above, the difference between UCCSD 1 and OO-UCCD 1 essentially comes from the order dependency of the doubles. Indeed, Grimsley et al reported that the typical doubles-operator-order dependency results in an energy difference of an order of less than a microhartree for UCCSD 1 near the equilibrium geometry for LiH, whereas the magnitude of the order-dependency increases with an increase in the LiH bond length [81]. Our results are consistent with theirs.…”
Section: A Without the Active Space Approximationsupporting
confidence: 92%
See 2 more Smart Citations
“…As mentioned above, the difference between UCCSD 1 and OO-UCCD 1 essentially comes from the order dependency of the doubles. Indeed, Grimsley et al reported that the typical doubles-operator-order dependency results in an energy difference of an order of less than a microhartree for UCCSD 1 near the equilibrium geometry for LiH, whereas the magnitude of the order-dependency increases with an increase in the LiH bond length [81]. Our results are consistent with theirs.…”
Section: A Without the Active Space Approximationsupporting
confidence: 92%
“…The double excitation operatorsT n = t rs pqĉ † pĉ † qĉ rĉs are generated so that the index strings psqr are in lexicographical order, where t rs pq is a doubles amplitude. Although Grimsley et al have illustrated that the effect of the operator ordering could be significant, their results suggest that the impact of the ordering is not important in the systems used in this study [81].…”
Section: Numerical Examplesmentioning
confidence: 57%
See 1 more Smart Citation
“…The COBYLA (Powell, 1994) algorithm was used as a gradient-free optimizer, while gradient-based optimizations were carried out with the L-BFGS algorithm (Nocedal, 1980;Liu and Nocedal, 1989), with all parameters being initialized at 0 at each optimization cycle for both optimizers. Other approaches have been reported in the literature, such as random initialization (Grimsley et al, 2020), or as in the original implementation of ADAPT-VQE (Grimsley et al, 2019) where the new parameter is initialized at 0, while the previous parameters are initialized from the optimal values obtained in the previous ADAPT iteration. XACC offers both optimizers via its interface with NLOpt (Johnson).…”
Section: Computational Detailsmentioning
confidence: 99%
“…It has been discussed recently that the Pauli operator ordering in the Trotterized circuits of the VQE-UCCSD approach can introduce significant errors in energy evaluations beyond chemical accuracy. 36 As a Trotterized form is also adopted in the smQITE method, similar operator ordering effects could exist. Nevertheless, we will demonstrate that decent numerical results from smQITE calculations can already be obtained without exploiting optimum Pauli operator orderings.…”
Section: Step-merged Qitementioning
confidence: 99%